The influence of application of complexes of power exercises on indicators of special force of muscles of a shoulder-girdle of sportsmen of the Paralympic national team of Ukraine on cross-country skiing and biathlon during the preparatory period - V'yacheslav Mulik; Andriy Nesterenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: the analysis of dynamics of power indicators of Paralympic sportsmen in the preparatory period of a year macrocycle when using complexes of power exercises in the training process which are aimed at the development of muscles of a shoulder-girdle. Material and Methods: members of the national Paralympic team of Ukraine on cross-country skiing and biathlon of two nosology (musculoskeletal device and visual impairment) in number of 12 sportsmen (6 men, 6 women) took part in the research. The age of sportsmen is 17-29 years old, the sports qualification is CMS (2), MS (4), MSIC (3), and MMS (3). Results: the technique of application of complexes of power exercises of high-speed and power character for muscles of a shoulder-girdle depending on stages of the preparatory period is developed and proved. The results of testing testify to the positive dynamics of indicators, especially at the end of the preparatory period. Conclusions: authors offer the technique of power training of Paralympic sportsmen on the basis of the conducted research, which is based on the use of complexes of special power exercises.